Dictionary of environmental science and technology - Porteous, Andrew (Hoboken, New Jersey : John Wiley & Son, Inc., 2008)
This dictionary includes over 4000 in-depth entries on scientific and technical terminology associated with environmental protection and resource management. In addition, it contains numerous illustrations, a wide range of international case studies and extensive cross-references to guide the reader.
The Dictionary -- Appendix I -- Appendix II -- Appendix III -- Appendix IV.
Keywords: DICTIONARIES